Poultry feather disulphide bond breakdown to enable bio-based polymer production. Issue 3 (August 2021) - McGauran, Thomas; Dunne, Nicholas; Smyth, Beatrice M.; Cunningham, Eoin; Harris, Matt
With oil supplies, needed for plastic production, decreasing dramatically, there is a clear driver for alterative polymers from sustainable resources. Poultry feathers, containing ∼90% keratin, are one source of natural polymer with huge potential for biopolymer production. However, the presence of crosslinks, known as disulphide bonds, hinders processability. This paper reviews techniques to enable breakage of disulphide bonds through use of reduction agents (sodium sulphite and sodium sulphate) and hydrolysis. Samples were analysed using FTIR and DSC to quantify achievable bond breakage, effect on thermal properties and changes in protein concentration. A review on the effect of particle size on disulphide bond breakage was also conducted, along with quantifying the reformation of bonds post-processing. Finally, a bicinchoninic acid (BCA) protein assay was used to quantify changes to soluble protein content, key to predicting if biopolymer formation can occur. The results showed a final disulphide bond breakage of between 48% and 67% was achievable using these techniques. It was also shown that disulphide bond content exhibited up to 60% bond reformation post treatment. These reductions in disulphide bonds increased the thermoplastic nature and apparent protein content. Despite achieving the highest bond breakage percentage, hydrolysis caused degradation of useful proteins, rendering the material unsuitable for biopolymer production. Results suggested that treatment with sodium sulphite (4.3% wt. of feathers) and use of a small particle size (0–100 µm), sufficiently altered the properties of raw feathers to enable feather biopolymer production.